2019
DOI: 10.1039/c8ra10164g
|View full text |Cite
|
Sign up to set email alerts
|

Praseodymium promotes B–Z transition in self-assembled DNA nanostructures

Abstract: Millimolar concentrations of PrCl3 can induce sequence-specific B–Z transition in various-self-assembled branched DNA (bDNA) nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Lanthanide-mediated DNA condensation and structural transition have been reported. 29,35,36 Moreover, it has been proved that monovalent cations stabilize multiplex DNA structures by reducing electrostatic repulsion, thereby increasing the melting temperature. 34 When bDNA USA-1 was denatured in the presence of Na + and K + , the T m increased with increase in cation concentration from 1 mM to 500 mM (Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanide-mediated DNA condensation and structural transition have been reported. 29,35,36 Moreover, it has been proved that monovalent cations stabilize multiplex DNA structures by reducing electrostatic repulsion, thereby increasing the melting temperature. 34 When bDNA USA-1 was denatured in the presence of Na + and K + , the T m increased with increase in cation concentration from 1 mM to 500 mM (Figure 4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…On the other hand, addition of 10 mM chloride salts of La or Ce caused a similar bDNA condensation observed through band shifting in agarose gel. Lanthanide-mediated DNA condensation and structural transition have been reported. ,, Moreover, it has been proved that monovalent cations stabilize multiplex DNA structures by reducing electrostatic repulsion, thereby increasing the melting temperature …”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the kinetics of the Z ‐conformer formation of dsDNA and dsRNA is greatly enhanced by the presence of overhangs and loops in a length‐dependent manner. Interestingly, similar observations have been reported that the B‐Z transition induced by salts such as LaCl 3 is influenced by loops and overhangs, resulting in significantly reduced salt concentrations required for reaching the full B‐Z transition of self‐assembled DNA nanostructures . Why unpaired single‐stranded regions facilitate the formation of Z conformers?…”
Section: The Observed Rate Constants Of the Hzαadar1‐induced B‐z Tranmentioning
confidence: 98%
“…Significant factors influencing the B-Z transition have been identified, such as alternating (CG) n sequences, high salt concentrations, multivalent cations or polycations, and Z binding proteins [14,[80][81][82][83]. In addition, steric effects are also important.…”
Section: Z-dnamentioning
confidence: 99%